MARKET RESEARCH: HITAMNYA KOPI INDONESIA DI PASAR KOREA - Arief Fadillah (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2008)
The world production of coffee annually continued to stable at the level of 117 million bags with an average volume of 60 kg in the period 2004-2007 and Indonesia is one of the world coffee producer. Korea is one of the countries that experienced an increase in the consumption of coffee, which is showed from the increasing import value of coffee. The needs of coffee is met by some importing countries such as Vietnam, Colombia, Brazil, Honduras, USA, and Indonesia as the 13th importing country. The export of Indonesia’s coffee to Korea is using other countries as third parties and tends to decrease. In addition, Indonesia has not been able to take the advantage market opportunities in Korea because of the technology and standard problems in the Indonesia’s coffee industry.